Efektivitas Penyelenggaraan Pelayanan Publik di Kelurahan Tondonggeu Kecamatan Nambo Kota Kendari - Asraf; La Ode Jumadil; Dedy Takdir Syaifuddin (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the effectiveness of public services in Tondonggeu Subdistrict, Nambo District, Kendari City, focusing on six main indicators, namely procedures, completion time, service fees, service products, facilities and infrastructure, as well as the competence of service officers. This research employed a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews, direct observation, and documentation, and were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results indicate that public service delivery in Tondonggeu Subdistrict has generally been quite effective. Service procedures are in line with the established standards, although they are still perceived as complicated. Completion time is relatively on target, though sometimes hindered by unstable internet networks. Service fees are transparent and free of charge, while service products are accurate and legally valid. Facilities and infrastructure are available but remain limited, whereas the competence of service officers is fairly good in terms of ethics and communication but still requires improvement in digital skills